Birth weight, weight over the adult life course and risk of breast cancer. Issue 1 (18th October 2019) - Luo, Juhua; Chen, Xiwei; Manson, JoAnn E.; Shadyab, Aladdin H.; Wactawski‐Wende, Jean; Vitolins, Mara; Rohan, Thomas E.; Cheng, Ting‐Yuan D.; Zhang, Zhenzhen; Qi, Lihong; Hendryx, Michael
Abstract : Breast cancer has been suggested to potentially have prenatal origins. We examined associations between birth weight, body mass index (BMI) at four‐time points over 25 years of adulthood, and risk of postmenopausal breast cancer, with emphasis on whether the association between birth weight and risk of breast cancer was mediated by weight and height changes over the adult life course. Postmenopausal women ( n = 70, 397) aged 50–79 years without breast cancer at enrollment (1993–1998) were followed up to 25 years. Weight and height were measured at baseline. Birth weight, and weights at ages 18, 35 and 50 were self‐reported. Breast cancer cases were centrally adjudicated. Compared to women with birth weight of 6–8 pounds, women with birth weight of <6 pounds had lower risk of breast cancer (HR = 0.88 95% CI: 0.79–0.99). 44% and 21% of the relationship between birth weight and breast cancer risk was mediated by adult height and weight at baseline, respectively. Birth weight of 8 pounds or more was not associated with risk of postmenopausal breast cancer. Weight gain in adulthood was associated with increased risk of breast cancer regardless of time periods. In conclusion, lower birthweight was associated with lower risk of postmenopausal breast cancer, and this reduction in risk was significantly mediated by childhood or adolescent growth, especially by adult height. Our data suggest that reaching and maintaining a healthy weight during adulthood is key in the prevention of breast cancer. Abstract : What's new? Higher birthweight is associated with increased risk of breast cancer, especially in premenopausal women. In this study, the authors analyzed the effect of adult weight and height on the association between birthweight and postmenopausal breast cancer. They enrolled 70, 397 postmenopausal women and monitored their breast cancer incidence over a 25‐year follow up. Women under 6 pounds at birth had reduced cancer risk, but more than 40% of this effect was mediated by adult height. High birthweight was not associated with postmenopausal breast cancer risk. Adult weight gain was associated with increased risk, regardless of birthweight.